Inter-Limb Muscle Synergies and Kinematic Analysis of Hands-and-Knees Crawling in Typically Developing Infants and Infants With Developmental Delay - Xiong, Qi L.; Wu, Xiao Y.; Yao, Jun; Sukal-Moulton, Theresa; Xiao, Nong; Chen, Lin; Zheng, Xiao L.; Liu, Yuan; Hou, Wen S. (Frontiers in Neurology, 2018)
The aim of this study was to quantify and compare inter-limb muscle synergy and kinematics during crawling between typically developing (TD, N=20) infants, infants at risk of developmental delay (ARDD, N=33), or confirmed developmental delay (CDD, N=13). Surface electromyography of eight arm and leg muscles and the corresponding joint kinematic data were collected while participants were crawling on hands and knees at their self-selected velocity. The inter-limb muscle synergy during crawling was extracted by nonnegative matrix factorization algorithm, and the structure of muscle synergy was quantified by the number of co-activation muscles per synergy. Temporal-spatial parameters and normalized Jerk-Cost (JC) function (i.e. smoothness of movement) were also computed from the measured kinematics. Then, we examined the relationship between muscle synergy and kinematic indices. Fewer muscle synergies and more co-activation muscles per synergy were found in the infants with CDD compared to infants with TD and ARDD, which suggests a constrained neuromuscular control strategy due to neurological injury in infants with CDD. The infants with CDD demonstrated higher normalized JC values (less movement smoothness) compared to infants with TD and ARDD. Furthermore, the normalized JC values were correlated with the number of co-activation muscles per synergy in infants with CDD, suggesting that higher co-activations across muscles may contribute to the reduced movement smoothness in infants with developmental delay. Metrics such as muscle synergy and kinematics may be useful to assess developmental delay in infants during the crawling stage before they are able to walk for traditional gait analysis assessments. This can aid in early identification of motor delays as well as an outcome measure for evaluating intervention progress.